2021
DOI: 10.1021/acs.jctc.0c01003
|View full text |Cite
|
Sign up to set email alerts
|

Relative Resolution: A Computationally Efficient Implementation in LAMMPS

Abstract: Recently, a novel type of a multiscale simulation, called Relative Resolution (RelRes), was introduced. In a single system, molecules switch their resolution in terms of their relative separation, with near neighbors interacting via fine-grained potentials yet far neighbors interacting via coarse-grained potentials; notably, these two potentials are analytically parameterized by a multipole approximation. This multiscale approach is consequently able to correctly retrieve across state space, the structural and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 62 publications
3
31
0
Order By: Relevance
“…While RelRes does not at all reduce the number of degrees of freedom, it definitively reduces the number of interactions for calculation: as compared with conventional strategies, the short-range interactions between near neighbors are inherently unaltered, yet the long-range interactions between far neighbors are prominently transformed from many FG potentials to few CG potentials; the significant decrease in the number of the latter means that the computer spends less time in calculating them. The fact that RelRes markedly speeds up molecular simulations by almost an order of magnitude was recently proven in LAMMPS. , In particular, we implemented RelRes in LAMMPS for the LJ potential, and we thoroughly demonstrated that it can correctly describe the static and dynamic behavior of various liquid alkanes, including oligomers and polymers . For all systems that we examined, RelRes enhanced the computational efficiency by a factor of 4–5 as compared with conventional strategies.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…While RelRes does not at all reduce the number of degrees of freedom, it definitively reduces the number of interactions for calculation: as compared with conventional strategies, the short-range interactions between near neighbors are inherently unaltered, yet the long-range interactions between far neighbors are prominently transformed from many FG potentials to few CG potentials; the significant decrease in the number of the latter means that the computer spends less time in calculating them. The fact that RelRes markedly speeds up molecular simulations by almost an order of magnitude was recently proven in LAMMPS. , In particular, we implemented RelRes in LAMMPS for the LJ potential, and we thoroughly demonstrated that it can correctly describe the static and dynamic behavior of various liquid alkanes, including oligomers and polymers . For all systems that we examined, RelRes enhanced the computational efficiency by a factor of 4–5 as compared with conventional strategies.…”
Section: Introductionmentioning
confidence: 76%
“…23−32 One such algorithm is called Relative Resolution (RelRes), and its main signature is that it switches between the FG and CG molecular resolutions based on the relative separation: for near neighbors, molecules experience the FG potential, and for far neighbors, molecules experience the CG potential. 29,31 The general approach was initially conceived by Izvekov and Voth, and they applied it on several liquids, most notably on an aqueous solution of a lipid bilayer; 29 Shen and Hu effectively continued applying this variant on other biomolecular systems (it appears that the original formalism was not properly referenced). 30 Chaimovich et al then made a couple of important modifications in the preliminary RelRes framework.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale Atoms/Molecular Massively Parallel Simulator (LAMMPS) software was used for performing molecular dynamics (MD) simulation. Herein, we put 1220 water molecules into MK using Packmol software (Figure a 2 ).…”
Section: Models and Simulation Detailsmentioning
confidence: 99%
“…The tension tests of the Al/Si vertically cracked nanofilm/substrate systems were conducted using an atomistic simulation program called the LAMMPS [17][18][19]. In atomic computational simulations, the potential energy of the atoms constituting the simulation models is crucial because the potential energy affects the interactions of the atomic bonds in the simulation models.…”
Section: Details Of Atomistic Simulationsmentioning
confidence: 99%